Der Prozess Jesu - aus r?omisch-rechtlicher Perspektive. - Paulus, Christoph G. (De Gruyter, 2016)
Although it is clear that the trial of Jesus has been extensively discussed and described before, new aspects are revealed by a strict focus on the written text from the perspective of legal history. The author follows this approach and comes to the inexorable conclusion that Jesus's sentence was fully consistent with the terms of Roman penal and procedural law.
Keywords: Law.; Electronic books.